2021
DOI: 10.1038/s41398-021-01757-1
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in neuronal systems function and behaviour: beyond a single diagnosis in autism spectrum disorders

Abstract: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder that is associated with functional brain alterations that underlie the expression of behaviour. Males are diagnosed up to four times more than females, and sex differences have been identified in memory, cognitive flexibility, verbal fluency, and social communication. Unfortunately, there exists a lack of information on the sex-dependent mechanisms of ASD, as well as biological markers to distinguish sex-specific symptoms in ASD. This can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 143 publications
0
10
0
1
Order By: Relevance
“…The interest on possible environmental agents which would be associated with development of ASD increased for last decades (Lawler et al, 2004). Lipopolysaccharide (LPS) is obtained from the walls of gram‐negative bacteria and has been demonstrated to be a good candidate for producing infection in animal models (American Psychiatric Association, 2013; Williams et al, 2021). The data have shown that administration of LPS during the perinatal period alters long‐term behavioral patterns, including abnormal social communication and disturbed socialization skills (Arsenault et al, 2014; Lawler et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The interest on possible environmental agents which would be associated with development of ASD increased for last decades (Lawler et al, 2004). Lipopolysaccharide (LPS) is obtained from the walls of gram‐negative bacteria and has been demonstrated to be a good candidate for producing infection in animal models (American Psychiatric Association, 2013; Williams et al, 2021). The data have shown that administration of LPS during the perinatal period alters long‐term behavioral patterns, including abnormal social communication and disturbed socialization skills (Arsenault et al, 2014; Lawler et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, sex dimorphism has been identified in the symptoms and diagnosis of ASD. Before adolescence, ASD is fourfold more frequent in male than female patients (de Giambattista et al., 2021), whereas during adolescence, the diagnosis is more frequent in female patients (Williams et al., 2021). These differences have been attributed to social and biological factors that may modify neural development between the sexes (Lai et al., 2015; Wood‐Downie et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A clear bias favouring males across various research stages contributes to this issue Lee [2018]. It is a crucial biological variable in dementia research Podcasy and Epperson [2016], the diagnosis of Autism Spectrum Disorder is up to four times more frequent in males than in females Williams et al [2021]. Therefore, recognizing sex as a crucial biological variable in primary and preclinical research is essential for ensuring accurate and reproducible results for diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%